2012
DOI: 10.1111/j.1600-065x.2012.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NF‐κB by the CARD proteins

Abstract: Summary:  Scaffold proteins play pivotal roles in the regulation of signal transduction pathways by connecting upstream receptors to downstream effector molecules. During the last decade, many scaffold proteins that contain caspase‐recruitment domains (CARD) have been identified. Investigating the roles of CARD proteins has revealed that many of them play crucial roles in signaling cascades leading to activation of nuclear factor‐κB (NF‐κB). In this review, we discuss the contributions of CARD proteins to NF‐κ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 156 publications
(253 reference statements)
0
85
0
Order By: Relevance
“…The PKC-CBM axis also mediates EGFR-induced NF-kB activation, as we have previously shown (18). Thus, our study reveals a shared mechanism by which the CBM complex mediates NF-kB activation in response to activation of the receptors in the EGFR family, and possibly activation of other types of tyrosine kinase receptors such as fibroblast growth factor receptor, which also activates PKC (14). Further investigation is needed to determine whether the CBM complex mediates NF-kB activation when other types of tyrosine kinase receptors are activated.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The PKC-CBM axis also mediates EGFR-induced NF-kB activation, as we have previously shown (18). Thus, our study reveals a shared mechanism by which the CBM complex mediates NF-kB activation in response to activation of the receptors in the EGFR family, and possibly activation of other types of tyrosine kinase receptors such as fibroblast growth factor receptor, which also activates PKC (14). Further investigation is needed to determine whether the CBM complex mediates NF-kB activation when other types of tyrosine kinase receptors are activated.…”
Section: Discussionmentioning
confidence: 57%
“…The CBM complex recruits E3 ligases such as TRAF6 to activate IKK complex via ubiquitination in response to TCR stimulation (13). Similarly, CARMA3 is mainly expressed in the nonhematopoietic cells and is required for protein kinase C (PKC)-induced NF-kB activation, in which CARMA3 forms the CBM complex through a similar mechanism as that of CARMA1 (14)(15)(16). In our previous studies, we found that the CBM complex is required for G protein-coupled receptor (GPCR)-and EGFR-induced NF-kB activation (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The NF-kB family of transcription factors plays a crucial role in cell activation, survival, and proliferation. Aberrant NF-kB activity results in cancer, immunodeficiency, or autoimmune disorders (such as psoriasis) (Lippens et al, 2011;Jiang and Lin, 2012). Recent studies have reported an association between common SNPs and several rare mutations in the CARD14 and psoriasis (Fuchs-Telem et al, 2012;Jordan et al, 2012a,b).…”
Section: Discussionmentioning
confidence: 99%
“…24e26 Caspase recruitment domain (CARD)-containing proteins are conserved across many species and are characterized by the presence of different functional domains shared between family members. 27 Structurally, CARD10, CARD11, and CARD14 (also known as CARMA3, CARMA1, and CARMA2) contain a CARD and a coiled-coil domain located at their aminoterminus, followed by a PDZ domain, then a SRC homology 3 (SH3) domain and a guanylate kinase-like (GUK) domain, which together constitute the membrane-associated GUK region at the carboxy-terminus. After phosphorylation, CARD proteins undergo conformational change that enables association with the downstream signaling components B-cell lymphoma protein 10 (BCL10) and mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1).…”
mentioning
confidence: 99%
“…Formation of the complex CARD/BCL10/MALT1 is believed to be an essential step for triggering the subsequent events that lead to activation of NF-kB. 27 CARD11 is essential for antigen receptoremediated NF-kB activation in lymphocytes, 28 and mutations in the CARD and coiled-coil domains are prevalent in diffuse large B-cell lymphoma (DLBCL), leading to hyperactive NF-kB signaling and increased cell survival. 29e32 In this study, we present data supporting a tumorigenic role for CARD11 in human epidermis.…”
mentioning
confidence: 99%